2016
DOI: 10.14348/molcells.2016.2288
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Causes of Inherited Peripheral Neuropathies by Targeted Gene Panel Sequencing

Abstract: Inherited peripheral neuropathies (IPN), which are a group of clinically and genetically heterogeneous peripheral nerve disorders including Charcot-Marie-Tooth disease (CMT), exhibit progressive degeneration of muscles in the extremities and loss of sensory function. Over 70 genes have been reported as genetic causatives and the number is still growing. We prepared a targeted gene panel for IPN diagnosis based on next generation sequencing (NGS). The gene panel was designed to detect mutations in 73 genes repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 25 publications
0
26
1
Order By: Relevance
“…The PMP22 duplication/deletion mutations, accounting for 23.3% of demyelinating CMT in Japan,8 were not involved in this study and were removed from the original data of previous studies to facilitate comparison. Consequently, we found that three genes, GJB1 , MFN2 , and MPZ , were the leading reasons in the present study, using data from Germany,9 USA,10 UK,11 Norway12 and Denmark13 studies; however, these results differ from previous reports from Japan,8 Spain,14Italy,15 Korea16 and a cross-country study 17. Particularly, in the other Japanese study,8 regarding other genes with mutation frequency higher than 1%, PMP22 (3.3%), NEFL (2.7%) and PRX (1.7%) have been reported, whereas we detected HSPB1 (1.4%) and PMP22 (1.3%) in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The PMP22 duplication/deletion mutations, accounting for 23.3% of demyelinating CMT in Japan,8 were not involved in this study and were removed from the original data of previous studies to facilitate comparison. Consequently, we found that three genes, GJB1 , MFN2 , and MPZ , were the leading reasons in the present study, using data from Germany,9 USA,10 UK,11 Norway12 and Denmark13 studies; however, these results differ from previous reports from Japan,8 Spain,14Italy,15 Korea16 and a cross-country study 17. Particularly, in the other Japanese study,8 regarding other genes with mutation frequency higher than 1%, PMP22 (3.3%), NEFL (2.7%) and PRX (1.7%) have been reported, whereas we detected HSPB1 (1.4%) and PMP22 (1.3%) in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Because of the large number of genes implicated in this heterogeneous group of disease, this and other studies [22,23,24,25] together highlight the practical advantage of high-throughput sequencing in rapidly reaching the specific genetic diagnosis over previously proposed stepwise diagnostic algorithms [26,27,28]. As illustrated in Case 1, the patient had undergone screening for PMP22 duplication, mutation of GJB1 and MFN2 and active investigation for more than two years before the gene-panel method was attempted.…”
Section: Discussionmentioning
confidence: 94%
“… 32 Therefore, it remains unclear whether the p.T54I variant is really pathogenic. Moreover, DCTN1 variants have been reported in primary lateral sclerosis, 34 neuropathy 35 and complex neurological disease with a slowly progressive, chronic axonal-distal motor neuropathy and extrapyramidal syndrome. 36 The case of extrapyramidal syndrome presented with ataxia, and also had NEFH and KIF5A variants.…”
Section: Resultsmentioning
confidence: 99%